Economic burden of resected (stage IB-IIIA) non-small cell lung cancer in France, Germany and the United Kingdom: A retrospective observational study (LuCaBIS). (October 2018) - Andreas, Stefan; Chouaid, Christos; Danson, Sarah; Siakpere, Obukohwo; Benjamin, Laure; Ehness, Rainer; Dramard-Goasdoue, Marie-Hélène; Barth, Janina; Hoffmann, Hans; Potter, Vanessa; Barlesi, Fabrice; Chirila, Costel; et al.
Highlights: This study estimated burden and cost-of-illness associated with resected NSCLC. The largest costs were dependent on therapy type, hospitalization and emergency costs. Monthly direct costs were the highest during distant metastasis/terminal illness phase. In the UK, monthly direct costs were the highest during the adjuvant treatment period. NSCLC accumulated large annual national costs, mainly during disease progression. Abstract: Objectives: New adjuvant treatments are being developed for patients with resected non-small cell lung cancer (NSCLC). Due to scarcity of real-world data available for treatment costs and resource utilization, health technology and cost-effectiveness assessments can be limited. We estimated the burden and cost-of-illness associated with completely resected stage IB-IIIA NSCLC in France, Germany and the United Kingdom (UK). Materials and methods: Eligible patients were aged ≥18 years with completely resected stage IB-IIIA NSCLC between August 2009 and July 2012. Patients (living or deceased) were enrolled at clinical sites by a systematic sampling method. Data were obtained from medical records and patient surveys. Direct, indirect and patient out-of-pocket expenses were estimated by multiplying resource use by country-specific unit costs. National annual costs were estimated based on disease prevalence data available from published sources. Results: 39 centers provided data from 831 patients of whom patient surveys were evaluable in 306 patients. Median follow-up was 26 months. The mean total direct costs per patient during follow-up were: €19, 057 (France), €14, 185 (Germany), and €8377 (UK). The largest cost drivers were associated with therapies received (€12, 375 France; €3694 UK), and hospitalization/emergency costs (€7706 Germany). Monthly direct costs per patient were the highest during the distant metastasis/terminal illness phase in France (€15, 562) and Germany (€6047) and during the adjuvant treatment period in the UK (€2790). Estimated mean total indirect costs per patient were: €696 (France), €2476 (Germany), and €1414 (UK). Estimates for the annual national direct cost were €478.4 million (France), €574.6 million (Germany) and €325.8 million (UK). Conclusion: To our knowledge, this is the first comprehensive study describing the burden of illness for patients with completely resected stage IB-IIIA NSCLC. The economic burden was substantial in all three countries. Treatment of NSCLC is associated with large annual national costs, mainly incurred during disease progression.